Measuring Islamic Legal Philosophy and Islamic Law: a Study of differences, typologies, and objects of study - Muhammad Fuad Zain; Ahmad Zayyadi (Jurnal Syariah dan Hukum Komparatif, 2023)
This paper explores the philosophy of Islamic law and Islamic law in terms of definition, object, and implementation. The two cannot be separated in the discourse of Islamic law. By understanding the two terms, will be wise in giving the law to a problem that arose both in classical times and now. Philosophy of Islamic Law with a philosophical approach uncovers fundamental issues conceptually, methodically, systematically, radically, universally, comÂprehensively, and rationally. Meanwhile, the law, within the framework of Islamic norms, is formal legislation and from customs recognized by the ummah. The objects and methods of Islamic legal philosophy are to achieve benefit and the ultimate goal of MaqaÌ„sid al-SyariÌ„Ê»ah and are analytical, epistemological, critical, rational, and comprehensive.